2009
DOI: 10.1068/b32133
|View full text |Cite
|
Sign up to set email alerts
|

The influence of weather on local geographical patterns of police calls for service

Abstract: Abstract. The effect of weather elements on the incidence of different types of crime has been the focus of a number of research studies. However, the detailed geographical dimension of this relationship has been largely ignored. The aim of this paper is to broaden the research on weather and crime to consider the effect of weather parameters on the spatial arrangement of crime within an urban area of the UK. A novel combination of techniques that are capable of both evaluating statistically and visualising ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 69 publications
3
53
1
Order By: Relevance
“…regular precipitation and seldom snowfall). The null effect of rain mirrors findings by other UK research (Field 1992;Brunsdon et al 2009). Whilst the magnitudes of the effects of temperature and wind speed in model 1 appear small, it should be noted that these conditions have a considerable rangefor example an increase of one km per hour in wind speed overall decreases robbery by 1.1 per cent.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…regular precipitation and seldom snowfall). The null effect of rain mirrors findings by other UK research (Field 1992;Brunsdon et al 2009). Whilst the magnitudes of the effects of temperature and wind speed in model 1 appear small, it should be noted that these conditions have a considerable rangefor example an increase of one km per hour in wind speed overall decreases robbery by 1.1 per cent.…”
Section: Resultssupporting
confidence: 65%
“…Using data from one weather station only approximates the weather across the study area, and as weather is known to vary enormously at the localised level (see Brunsdon et al 2009) it is certainly the case that there is some error in our measurements of weather. Further to this, relying on police-recorded data necessarily excludes unreported crimes; however this is true of all research using police data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other features of physical geography and their relationship with crime and disorder have been the subject of investigations by researchers for well over a century. For example, a large and growing body of literature has investigated the relationship between weather and crime (see Baumer & Wright, 1996;Brunsdon, Corcoran, Higgs, & Ware, 2009;Ceccato, 2005;Cohn & Rotton, 2000;Heller & 3 Markland, 1970). Despite some contradictions, researchers have found that crime rates generally display a seasonal pattern with property crimes typically peaking in winter, and crimes against the person peaking in the hot months of summer (Landau & Fridman, 1993;Van Koppen & Jansen, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…RA theory suggests that individuals generally follow fairly strict and regimented routines -daily, weekly, monthly or seasonal, and even yearly routines (Brunsdon, Corcoran, Higgs, & Ware, 2009). Essentially, the same periodicities that are found throughout nature and in society as a whole also exist in individual human behavior.…”
Section: Introductionmentioning
confidence: 99%